Criminal Law Policy in Efforts to Combat the Illegal Distribution of Hard Drugs Without a Doctor's Prescription - Kabanga, Yoshua Andres; Sopacua, Margie Gladies; Saimima, Judy Marria (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Nowadays, there are many irregularities related to the Health Act. The urgency of problem solving arising from medication errors is very great because one type of medication error, namely administration error, ranks first compared to other types of medication errors. With the percentage of administration errors amounting to 81.32% of errors related to medical administration that occur in Indonesia.Purposes of the Research:  To understand and explain the juridical responsibility that must be imposed on the perpetrators of selling prescription drugs without a doctor's prescription through online buying and selling sites.Methods of the Research: Research methods are used to find and process data in accordance with the research objectives and solve the problems posed by researchers.Results of the Research: The results showed that: (1). In Law Number 17 of 2023 concerning Health (hereinafter referred to as the Health Law) there are offenses that can be imposed on the perpetrator, these offenses are listed in Article 435 & Article 436. Article 435 states that every violation of medication error will be sentenced to imprisonment for a maximum of 12 (twelve) years or a maximum fine of Rp5,000,000,000.00 (five billion rupiah). Meanwhile, a person who does not have the expertise in the field of pharmacy in accordance with the provisions of the Law but continues to distribute pharmaceutical preparations will be subject to the offense in article 436 with a maximum imprisonment of 5 (five) years or a maximum fine of Rp. 500,000,000.00 (five hundred million rupiah).” Countermeasures against prescription drugs without a doctor's prescription can basically be dealt with by article 435 and article 436 of the Health Law, and there is a lot of evidence of the existence of these two articles that apply to offline prescriptions drug dealers.  (2). Countermeasures against the distribution of prescription drugs through online buying and selling sites are still somewhat ambiguous because there is no law that specifically regulates the countermeasures of prescription drugs online, which causes a legal vacuum in countermeasures against the distribution of prescription drugs online. Therefore, elaboration, and hard work from every law enforcement officer is needed to tackle the problem.